Characterization of a cyanobacterial rep protein with broad-host range and its utilization for expression vectors - Sakamaki, Yutaka; Maeda, Kaisei; Nimura-Matsune, Kaori; Chibazakura, Taku; Watanabe, Satoru (Frontiers in Microbiology, 2023)
Owing to their photosynthetic capabilities, cyanobacteria are regarded as ecologically friendly hosts for production of biomaterials. However, compared to other bacteria, tools for genetic engineering, especially expression vector systems, are limited. In this study, we characterized a Rep protein, exhibiting replication activity in multiple cyanobacteria and established an expression vector using this protein. Our comprehensive screening using a genomic library of Synechocystis sp. PCC 6803 revealed that a certain region encoding a Rep-related protein (here named Cyanobacterial Rep protein A2: CyRepA2) exhibits high autonomous replication activity in a heterologous host cyanobacterium, Synechococcus elongatus PCC 7942. A reporter assay using GFP showed that the expression vector pYS carrying CyRepA2 can be maintained in not only S. 6803 and S. 7942, but also Synechococcus sp. PCC 7002 and Anabaena sp. PCC 7120. In S. 7942, GFP expression in the pYS-based system was tightly regulated by IPTG, achieving 10-fold higher levels than in the chromosome-based system. Furthermore, pYS could be used together with the conventional vector pEX, which was constructed from an endogenous plasmid in S. 7942. The combination of pYS with other vectors is useful for genetic engineering, such as modifying metabolic pathways, and is expected to improve the performance of cyanobacteria as bioproduction chassis.